AVALIAÇÃO DA ESTABILIDADE, LIBERAÇÃO E PERMEAÇÃO CUTÂNEA DE NANOCÁPSULAS CONTENDO BENZOFENONA-3 - Roggia, Isabel (2009)
The nanocosmetic products can contain nanostructured actives, presenting superior properties in relation to the conventional cosmetics, improving already existing formulations, increasing and its safety and effectiveness. Is this way, the sunscreens have been extensively investigated, due to its frequent and prolonged use. This work presents as main objective evaluate the in vitro release and skin permeation of the benzophenone-3 in polymeric nanoparticles, incorporated in different semi-solid formulations using, as membrane, cellulose acetate and abdominal human skin, respectively. This work also included physico-chemical stability studies, assessment of organoleptic characteristic, rheological assessment and determination of the term validity. The dosage technique of BZ3 in spectrophotometer was validated in all analyzed parameters and the results obtained met the specifications for linearity, precision, robustness and accuracy. The BZ3 concentration in the semi-solid formulations decreased for all formulations in the course of the experiment, both the nanoencapsulated BZ3 as in the free. The organoletptic characteristics and the pH were kept for all the formulations in study. The viscosity values did not altered for the formulations of hydrogel (HGNCBZ3) and gel cream (CGNCBZ3) containing encapsulated BZ3. The viscosity for hydrogel formulation containing BZ3 in the free form (HGBZ3) presented a significant increase. The spreading values remained stable for all the tested formulations, both for the nanoencapsulated active as in the free form. The formulations containing nanoencapsulated BZ3 presented greater term validity than formulations with BZ3 in the free form. Through studies of release was observed that the formulations containing BZ3 in the form encapsulated presented a lower release than free form. The formulations containing BZ3 in the free form, did not present a significant difference for the flow values in the different vehicles. It was still observed, that the BZ3 incorporated in the HGNCBZ3 presented a greater releasing flow, when compared with CGNCBZ3 and ESNCBZ3, showing that the vehicle may to influence in the behavior of the nanocarrier release. The skin permeation of the BZ3 incorporated in the gel cream was similar as much for the free form as encapsulated. The encapsulated BZ3 presented a greater concentration in the cornea extract. These results correspond to those found by Paese (2008) when the experiments were performed using pig s membrane, reaffirming the interchangeability between the membranes used for the permeation studies with nanoestrutured systens.